HILLMAIL: A SECURE EMAIL SYSTEM FOR ANDROID-BASED MOBILE PHONE USING HILL CIPHER ALGORITHM - Tita Karlita; Isbat Uzzin Nadhori; Mohammad Azis Khoirul Fata (Universitas Trunojoyo Madura, 2016)
Nowadays, email has become the most widely communication way in daily life. Email is a very important method of communicating across the internet. During transmission and downloads, it uses protocols which are not secure. Spammers and scammers misuse these protocols to gain access to critical data stored in the email. This triggered concerns because sometimes email is used to exchange confidential messages. To improve security and efficiency of email system, we made an email security system for Android mobile phone using Hill Cipher algorithm. Hill Cipher is a classic cryptography algorithm that uses matrix inverse and matrix multiplication operations to hide the message. The initial stage of the encryption process is forming ciphertext by multiplying the key matrix with plaintext matrix. The contents of encrypted messages only can be read by legitimate recipient who has the key. Converting the ciphertext into plaintext is done by multiplying the ciphertext matrix with the inverse key matrix. The email content can be a plain message or a message with an attached file.